LncRNA TDRG1-Mediated Overexpression of VEGF Aggravated Retinal Microvascular Endothelial Cell Dysfunction in Diabetic Retinopathy - Gong, Qiaoyun; Dong, Wenpei; Fan, Ying; Chen, Feng’e; Bian, Xiaolan; Xu, Xun; Qian, Tianwei; Yu, Ping (Frontiers in Pharmacology, 2020)
Abstract Purpose: Diabetic retinopathy (DR), a neurovascular disease, is one of the leading causes of blindness in working-age adults. Long noncoding RNAs (lncRNAs) have attracted attention as indicators for DR. This study aimed to characterize the role of lncRNA human testis development–related gene 1 (TDRG1) and its modulation of vascular endothelial growth factor (VEGF) in deteriorating DR. Methods: Tissue samples were obtained from patients with epiretinal membranes (EMs) or proliferative DR, and human retinal microvascular endothelial cells (HRECs) were cultured with high-glucose medium to mimic DR as the in vitro model. The expression of lncRNA TDRG1 and VEGF was determined by immunofluorescence staining, Western blotting and RT-qPCR. Transfection of small-interfering RNA was conducted to knock down target gene expression. HREC functions were evaluated by cell viability, fluorescein isothiocyanate (FITC)-dextran extravasation, migration and tube formation assays under different conditions. Results: LncRNA TDRG1 and VEGF were found to be co-expressed and significantly upregulated in fibrovascular membranes (FVMs) from DR patients compared to those from EM patients. In the in vitro model, hyperglycemic treatment markedly increased the expression of lncRNA TDRG1 and VEGF at the mRNA and protein levels, which promoted cell proliferation and migration, enhanced permeability, and disrupted tube formation of HRECs. However, knockdown of lncRNA TDRG1 or VEGF notably decreased the expression of VEGF and reversed the impaired functions of high-glucose-treated HRECs. Conclusions: LncRNA TDRG1 promoted microvascular cell dysfunction via upregulating VEGF in the progression of DR and may serve as a potential therapeutic target in DR treatment.